Differential vascular α(1)-adrenoceptor antagonism by tamsulosin and terazosin - Schäfers, Rafael F (Blackwell Science Inc, 1999)
AIMS: In patients with lower urinary tract symptoms suggestive of benign prostatic obstruction the α(1)-adrenoceptor antagonist terazosin lowers blood pressure whereas only very small if any alterations were reported with the α(1)-adrenoceptor antagonist tamsulosin. Therefore, we have compared the vascular α(1)-adrenoceptor antagonism of tamsulosin and terazosin directly. METHODS: Ten healthy subjects were investigated in a randomized, single-blind, three-way cross-over design and received a single dose of 0.4 mg tamsulosin, 5 mg terazosin or placebo on 3 study days at least 1 week apart. Before and 1, 3, 5, 7, 10 and 23.5 h after drug intake, alterations of diastolic blood pressure and other haemodynamic parameters in response to a graded infusion of the α(1)-adrenoceptor agonist phenylephrine were determined non-invasively. RESULTS: At most time points tamsulosin inhibited phenylephrine-induced diastolic blood pressure elevations significantly less than terazosin (5 h time point: median difference in inhibition 35%, 95% CI: 18.7–50.3%). On the other hand, phenylephrine-induced changes of cardiac output, heart rate and stroke volume were similar during both active treatments. CONCLUSIONS: In doses equi-effective for treatment of lower urinary tract symptoms tamsulosin causes less inhibition of vasoconstriction than terazosin.